Principles and practice of translation in arabic (2012)
The paper intends to unfold the problems of methods and technicalities that hinder the success of Nigerian Arabic students in translating text from Arabic- English -Arabic. Therefore, opens its discussion with the kinds of Translation and meaning to be carefully observed in any translation job. It also highlights the four Ts of a translation Project coupled with the purpose of evaluation in a translation project .It emphasizes the role and the purpose of consultant in any translation project .Finally expatiates how initial and Final drafts are prepared in a translation project.